Alodínia mecânica e edema de pata induzidos por um ativador da proteína quinase C, PDD: caracterização e comparação com as respostas induzidas pela carragenina - Karina Abdo Costa (2004)
In vitro protein kinase C (PKC) activation releases inflammatory mediators and activates or sensitizes nociceptors. In vivo studies have demonstrated that PKC activation induces inflammation and is associated with the peripheral and spinal processing of the nociceptive response. However, a full characterization of the nociceptive response and edema induced by intraplantar (i.pl.) injection of a PKC activator has not been carried out. The present study aimed to characterize the mechanical allodynia and edema induced by i.pl. injection of a PKC activator in rats, to evaluate the role of different mediators (eicosanoids, 5-HT, histamine and NO) in the development of these responses and to compare the results with those induced by carrageenan. I.pl. injection of phorbol-12,13-didecanoate (PDD: 0.01 or 0.1 g), a PKC activator, or carrageenan (50 or 500 g), but not 4-PDD, an inactive analogue, induced mechanical allodynia and edema. The mechanical allodynia induced by PDD was partially inhibited by intraperitoneal (i.p.) injection of indomethacin (2 or 4 mg/Kg), L-NAME (100 mg/Kg) and the association indomethacin + L-NAME, but not dexamethasone (0.25 or 1 mg/Kg), rofecoxib (5 or 10 mg/Kg), methysergide (2 or 4 mg/Kg), promethazine (5 or 10 mg/Kg) or morphine (5 or 10 mg/Kg). The mechanical allodynia induced by carrageenan was inhibited by i.p. injection of indomethacin (2 or 4 mg/kg), rofecoxib (5 or 10 mg/Kg), L-NAME (100 mg/Kg), methysergide (4 mg/Kg) or morphine (5 or 10 mg/Kg). The edema induced by PDD was inhibited by i.p. injection of dexamethasone (0.25 or 1 mg/Kg), L-NAME (50 or 100 mg/Kg), methysergide (2 or 4 mg/Kg), promethazine (5 or 10 mg/Kg) or ketotifen (4 mg/Kg), but not indomethacin (2 or 4 mg/Kg). The edema induced by carrageenan was inhibited by the i.p. injection of dexamethasone (0.25 or 1 mg/Kg), indomethacin (2 or 4 mg/Kg), rofecoxib (5 or 10 mg/Kg), L-NAME (50 or 100 mg/Kg), methysergide (2 or 4 mg/Kg), but not promethazine (5 or 10 mg/Kg). Finally, i.pl. injection of indomethacin (50 or 100 g) or L-NAME (50 or 100 g) did not inhibit the mechanical allodynia induced by PDD. In conclusion, i.pl. injection of a PKC activator induces mechanical allodynia and edema, responses that probably result from the action of different mediators. In addition, these responses differ from those induced by carrageenan, since the drugs used affected differentially the responses induced by the two inflammatory stimuli.